The Relationship between EFL Students’ Use of Writing Strategies and Their Writing Achievement - Oussou, Said; Kerouad, Smail; Hdii, Saida (Jurnal Arbitrer, 2024)
Research on writing strategies has defined their characteristics and focused on their contribution to writing gains over the last few decades. However, little has been written about how Moroccan EFL students perceive and use these strategies in their attempts to produce an essay. This paper seeks to fill that gap by investigating the employment of writing strategies by 245 students majoring in English at a university. The data were collected through a questionnaire, inspired by some related existing scales, and interviews were conducted with a group of participants. The participants were sampled adhering to the convenience type of sampling since the data collection was completed in one of the students’ usual classes. Combining both quantitative and qualitative analyses, findings demonstrated that writing strategies were used to a higher extent, with the students’ strong tendency to deploy memory and compensation strategies. It was also found that there is a positive and significant correlation between students’ use of writing strategies and argumentative writing. The qualitative findings added that the although the participants said they practiced writing strategies, the majority did not know how to use them. Some implications and recommendations are also discussed. The current study has provided useful insights into students’ readiness to use writing strategies in the Moroccan context and how their use may mitigate their difficulties in producing a well-argued essay.